The effect of low level sulfide addition and the performance of precipitated- iron Fischer-Tropsch catalysts - Bromfield, Tracy Carolyn (My University, 2016)
Precipitated-iron Fischer- Tropsch catalysts were sulfided in the range 500 - 20000 ppm S/Fe with an aqueous sulfide source (Na2S, (NB4)zS, (NB4)zS5) during the precipitation process. Sulfidation was performed at pH 10.75, 8.5 and 6.9. Sodium ions were removed by centrifugation, and atomic absorption analysis confirmed low sodium levels (0-51 ppm). Based on solution speciation models, ferrous sulfide (FeS) which formed from aqueous HS' species, was found to influence the iron-oxyhydroxide crystallite morphology. It is proposed that, when sulfide was added at pH 10.75, FeS molecules functioned as nuclei for crystallite growth, while a pH 6.9 they assisted 'with the aggregation of particles. The processes of nucleation and aggregation appeared to be in competition following sulfidation at pH 8.5, resulting in a composite morphology that produced an inactive catalyst. The bulk structure of the catalysts was elucidated using XRD, SEM and nitrogen porosimetry, All sulfided catalysts exhibited enhanced BET surface areas and total pore volumes with a maximum at 2000 ppm S (surface area = 166 m2/g,total pore volume = 0.254 cm3/g) compared to an unsulfided catalyst (surface area = 58 m2/g, total pore volume = 0.184 cm3/g), Furthermore, for any series of catalysts at the same level of sulfidation, the BET surface areas were observed to decrease as the pH of sulfide addition decreased. Increasing levels of sulfidation (to 20000 ppm) brought about an increase in crystallite size and therefore, improved crystallinity as determined by XRD measurements. Materials with larger crystallites possess smaller surface areas, and thus the crystallinity was found to increase as the pH of sulfidation decreased. Surface characterisation by XPS after calcination at 400°C and reduction (400°C), revealed sulfate species (169.4 eV) on catalysts sulfided with 500-2000 ppm, while sulfide species (162.O eV) emerged at higher sulfide content. No sulfates were observed on reduced catalysts following calcination at 200 C. [Abbreviated Abstract. Open document to view full version]
A thesis submitted to the Faculty of Science, University of the Witwatersrand; Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. July 1991
Keywords: Chemical reactions; Catalysts; Fischer-Tropsch process; Sulfidation